Studies on Diversity of Natural Dye Yielding Plants of Birbhum and Burdwan Districts of West Bengal, India - Mandal, Subrata; Das, Uday (International Journal of Economic Plants, 2022)
The present study is based on extensive survey, collection of ethnobotanical information, indigenous knowledge and review of relevant literature on the traditional dye yielding plant resources used by the different tribal and rural peoples of Birbhum and Burdwan districts of West Bengal. Field investigation was carried out in different villages and adjacent forest pockets in these districts. Total 32 natural dye yielding plants were reported. These 32 taxa spread over 30 species, 29 genera and 22 families of dicotyledons and 2 species, 2 genera and 2 families of monocotyledons. Among the recorded plant species, 26 are found in wild and 6 are grown as cultivated crops and as garden plants. The investigated plants have been enumerated alphabetically depending upon their botanical names along with their local and tribal names, parts used, name of the dye etc. Some noteworthy dye yielding plants are- Bixa orellana, Butea monosperma, Calotropis gigantea, Carthamus tinctorius, Curcuma longa, Lawsonia inermis and Nyctanthes arbor-tristis. The data of this study can further be exploited by the workers in the fields of phytochemistry, genetics, food and textile industries, conservation biology, etc.